Contraceptives Knowledge and Perception: A Cross-Sectional Study Among Future Pharmacists in Jordan - Al-Shami KM; Al-Ashwal FY; Bitar AN; Alshakhshir S (Dove Medical Press, 2023)
Kamal M Al-Shami,1,2 Fahmi Y Al-Ashwal,3,4 Ahmad Naoras Bitar,5 Sami Alshakhshir6 1Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology, Irbid, Jordan; 2Division of Tumor Metabolism and Microenvironment, German Cancer Research Center, Heidelberg, Germany; 3Department of Clinical Pharmacy, College of Pharmacy, Al-Ayen University, Thi-Qar, Iraq; 4Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, University of Science and Technology, Sana'a, Yemen; 5Department of Clinical Pharmacy, Faculty of Pharmacy and Biomedical Sciences, Malaysian Allied Health Sciences Academy, Selangor, Malaysia; 6Department of Clinical Pharmacy, College of Pharmacy, Aqaba University of Technology, Aqaba, JordanCorrespondence: Fahmi Y Al-Ashwal, Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, University of Science and Technology, Sana'a, Yemen, Tel +967-771661055, Email fahmialashwal89@gmail.comBackground: Unintended pregnancy has huge burdens on healthcare resources and society. Contraception is essential to reduce it, and pharmacists are usually the first healthcare providers who are asked for advice about contraceptives. Therefore, the study aimed to evaluate future pharmacists' knowledge, awareness, and perceptions of contraceptive methods and assess the factors influencing their knowledge, awareness, and perceptions.Methods: This cross-sectional study was conducted among senior pharmacy ‎students at four universities. Data was collected over three months using a structured and validated questionnaire. Both inferential (Mann-Whitney U-test and Kruskal-Wallis test) and descriptive analyses were employed.Results: A total of 310 eligible participants completed the questionnaire, and more than half of them ‎‎(N=172; 55.5%) were final-year students. The Mann-Whitney U-test revealed that final-year students had significantly better knowledge (U= 14,261.5, p< 0.002) and a higher level of awareness (U= 13,971.5, p< 0.007) than fourth-year students. Interestingly, the Kruskal-Wallis test showed that the type of training (hospital, community, none) had a statistically significant impact on awareness scores (p< 0.001).Conclusion: Final-year students had higher knowledge and were more aware of contraception than fourth-year students. Also, community pharmacy training was associated with better awareness about contraceptives‎. Therefore, future studies should explore the impact of incorporating more targeted contraceptive education into earlier years of pharmacy education to bridge the knowledge gap observed between final-year and fourth-year students. Additionally, research should also investigate the effectiveness of specific community pharmacy training modules on contraceptive awareness.Keywords: awareness, attitude, contraceptives, pharmacy students